Phytic acid attenuates upregulation of GSK-3β and disturbance of synaptic vesicle recycling in MPTP-induced Parkinson's disease models. (October 2019) - Wang, Liping; Zhang, Zheng; Hou, Lin; Wang, YueHua; Zuo, JinHui; Xue, MeiLan; Li, XiangHong; Liu, YongChao; Song, JinLian; Pan, FengYu; Pu, TingWei
Abstract: Heightened activity of glycogen synthase kinase-3β (GSK-3β) is linked to the degeneration of dopaminergic neurons in Parkinson's disease (PD). Phytic acid (PA), a naturally occurring compound with potent antioxidant property, has been shown to confer neuroprotection on dopaminergic neurons in PD. However, the underlying mechanism remains unclear. In the present study, MPTP and MPP + treatments were used to model PD in mice and SH-SY5Y cells, respectively. We observed reduced tissue dopamine, disrupted synaptic vesicle recycling, and defective neurotransmitter exocytosis. Furthermore, expression of GSK-3β was upregulated while that of β-catenin was downregulated, concentration of cytosolic calcium was increased, and expressions of two dopamine carriers, dopamine transporter (DAT) and vesicular monoamine transporter 2 (VMAT2) were decreased. PA treatment attenuated the MPTP-induced upregulation of GSK-3β, increase in cytosolic calcium concentration, decreases in the levels of DAT, VMAT2, tissue dopamine, and synaptic vesicle recycling. Importantly, disturbances in synaptic vesicle recycling are thought to be early events in PD pathology. These findings suggest that PA is a promising therapeutic agent to treat early events in PD. Graphical abstract: Image 1 Highlights: Phytic acid was found to serve as GSK-3β inhibitor. It improved disturbance of synaptic vesicle recycling and defect of neurotransmitter release. It might be a promising medicine to treat early events in parkinson's disease.